2002
DOI: 10.1080/jmf.12.4.260.266
|View full text |Cite
|
Sign up to set email alerts
|

ST analysis of the fetal electrocardiogram during labor: Nordic observational multicenter study

Abstract: The STAN clinical guidelines identify fetuses at risk of intrapartum asphyxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…The current database has been analysed in another study regarding ST waveform changes in fetal ECG. 9 All the acidotic fetuses displayed an increase in T/QRS ratio, with ST segment elevation on average 24 (median), 18 -33 minutes (95th CI) before the end of recording. In the present study, the median time lag between the end of recording and delivery was 4 minutes, 1 -9 minutes (95th CI) in acidotic fetuses, of whom all but one were delivered vaginally.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…The current database has been analysed in another study regarding ST waveform changes in fetal ECG. 9 All the acidotic fetuses displayed an increase in T/QRS ratio, with ST segment elevation on average 24 (median), 18 -33 minutes (95th CI) before the end of recording. In the present study, the median time lag between the end of recording and delivery was 4 minutes, 1 -9 minutes (95th CI) in acidotic fetuses, of whom all but one were delivered vaginally.…”
Section: Methodsmentioning
confidence: 93%
“…Also, it has been applied as a marker of significant acidosis in previous studies on intrapartum asphyxia. 9,13,14 In the human fetus, acute hypoxia causes a small increase in fetal heart rate, but in severe acidosis fetal heart rate gradually declines, resulting in bradycardia. 15,16 The reduction in fetal heart rate variability in the presence of bradycardia appears to be a rather late sign of severe acidosis, 5,17 and is associated with reduced cerebral oxygen consumption and poor fetal outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Encouraging data demonstrate that intrapartum fetal ECG analysis can reduce newborn acidemia, hypoxic ischemic encephalopathy, [3] and cesarean deliveries. [4] However, the only clinically-available device for fetal ECG analysis – the STAN monitor from Neoventa -- requires an invasive fetal scalp electrode, limiting its use to a subset of pregnant women who are laboring with ruptured membranes and a dilated cervix.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of fetal electrocardiogram ST waveform analysis to conventional CTG (STAN ® , Neoventa, Gothenburg, Sweden) has been shown to increase the identification of fetuses with metabolic acidosis [9]. A systematic review of the first three trials comparing CTG+ST monitoring with conventional CTG showed that the former significantly decreases the rates of fetal blood sampling, neonatal encephalopathy and operative delivery, and is associated with a borderline reduction in the incidence of umbilical artery metabolic acidosis [10].…”
Section: Introductionmentioning
confidence: 99%